2018
DOI: 10.1016/j.foodres.2018.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the chemical, sensory and volatile composition of sapota-do-Solimões pulp at different ripening stages

Abstract: The aim of this study was to evaluate sapota-do-Solimões (Quararibea cordata Vischer) during ripening, verifying physical, chemical and sensory parameters, bioactive and volatile compounds. The pulps were obtained from fruits from the city of Tefé, AM, Brazil and collected at three different ripening stages: unripe (U); ripe collected from the tree (R); and ripe collected from the ground (RG). The biometric and quality parameters, total carotenoids, total phenolic compounds, chemical composition, fatty acids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The OS + V and US were below the threshold (≤70) for texture, odor, and taste, and based on Monteiro et al. (2018) hypothesis (IA ≥ 70%), they had a low acceptance. The taste results had the lowest score for all the attributes, which correlates with the 7‐point hedonic score (Table 5).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The OS + V and US were below the threshold (≤70) for texture, odor, and taste, and based on Monteiro et al. (2018) hypothesis (IA ≥ 70%), they had a low acceptance. The taste results had the lowest score for all the attributes, which correlates with the 7‐point hedonic score (Table 5).…”
Section: Resultsmentioning
confidence: 95%
“…Except for taste, the GBS products received a good IA for all parameters, based on Monteiro et al. (2018) hypothesis that an IA ≥ 70% is regarded as acceptable. ANOVA was applied to the various treatments, as shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total sugars showed significant differences between the pulp and formulations, but in percentages that exceed what could be attributed to the addition of the foam promoters, which must be explained by the natural variability of the mixed pulp samples. Monteiro et al (2018), studying Sapota-do-Solimões (Quararibea cordata Vischer) reported total sugar content of 4.2 g 100 -1 g, placing the samples of mixed pulp and the three formulations between common values determined in fruit pulps.…”
Section: Shaari Et Al (mentioning
confidence: 99%